Thermal varicose treatment under hypnosis - Josnin, Matthieu (Phlebologie, 2020)
Hypnosis has undergone great developments throughout the history of mankind. Medical hypnosis is a much more recent medical discipline that has been slow to be recognized as such. Today it has a well-defined place and there is no longer any doubt as to its effectiveness, as evidenced by its establishment in our services and the number of publications about it. The management of varicose veins of the lower limbs by thermal ablation is a very good indication for hypnosis, then called hypnoanalgesia. Practitioners who are well trained and experienced in hypnosis can use it during these procedures and bring undeniable comfort to their patients. A protocol is presented here adapted to the practice of this ablation procedure while meticulously following the principles of Ericksonian hypnosis.
Keywords: hypnosis; varicose vein; thermal ablation